2006
DOI: 10.1002/jms.1026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites of 4,4′‐methylenedianiline in vascular smooth muscle cells by liquid chromatography‐electrospray tandem mass spectrometry

Abstract: A capillary liquid chromatography-electrospray tandem mass spectrometry (LC-ES-MS/MS) method was developed for the identification of metabolites of 4,4'-methylenedianiline (diaminodiphenyl methane, (DAPM)) derived from exposure of vascular smooth muscle cells (VSMC) to this compound. The use of precolumn concentration and column switching techniques prior to reversed-phase liquid chromatography coupled online to ES-MS enabled the separation and detection of low-level DAPM and its metabolites in the exposed cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Though we did observe DAPM metabolites in these cells, they were the same acetylated metabolites as we had previously reported - N -acetyl DAPM and one minor metabolite as N,N ′-diacetyl DAPM (8). While we expect that neither of these metabolites were responsible for DAPM-induced toxic effects, to try and unveil whether other metabolites not yet detected might also be formed, we compared the disappearance of DAPM in COX-2 deficient as compared to wildtype cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Though we did observe DAPM metabolites in these cells, they were the same acetylated metabolites as we had previously reported - N -acetyl DAPM and one minor metabolite as N,N ′-diacetyl DAPM (8). While we expect that neither of these metabolites were responsible for DAPM-induced toxic effects, to try and unveil whether other metabolites not yet detected might also be formed, we compared the disappearance of DAPM in COX-2 deficient as compared to wildtype cells.…”
Section: Discussionsupporting
confidence: 85%
“…We observed 3 putative DAPM metabolites in these cells. In our prior studies (8), we had identified one as N -acetyl DAPM and one minor metabolite as N,N ′-diacetyl DAPM. On the assumption that a proximate toxicant of DAPM may be produced at levels below the detection limit or may be too rapidly conjugated to protein or other biomolecules so as to be difficult to detect, we compared the disappearance of DAPM in COX-2 deficient to that observed in wildtype cells (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The driving force for this process is likely the stability of the products: aniline can either remain neutral or further decompose to 77 Da as shown in Figure 2e,f, and the 106 Da fragment can further rearrange to a tropylium-like ion of the same mass. 7,39 This mechanism describes the metastable behavior of these ions; therefore, detection of o -NH 2 protonated 2,4′-MDA or 2,2′-MDA is minimal. As a result, the primary conformation observed for the 2,2′-MDA [M + H] + ion (199 Da) is composed of ring protonated species.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Acetylated metabolites were reported to be found in urine, blood and vascular smooth muscle cells. [10,11] However, their presence cannot explain the toxicity of DAPM. Other reactive and toxic metabolites are expected in bile, the likely route of exposure of bile duct cells to the proximate toxicant.…”
Section: Introductionmentioning
confidence: 99%